нужны ответы
19 вопрос
За ранее


нужны ответы 19 вопрос За ранее

Віка12341 Віка12341    3   21.06.2021 14:48    0

Ответы
УРВ05052001 УРВ05052001  21.07.2021 14:48

2

Пошаговое объяснение:

\frac{a+3}{a-3}-\frac{a-3}{a+3} = \frac{(a+3)^{2}}{a^2-9}-\frac{(a-3)^2}{a^2-9}=\frac{a^2+6a+9-a^2+6a-9}{a^2-9}=\frac{12a}{a^2-9}

\frac{12a}{a^2-9} + \frac{36}{a^2-9} =\frac{12(a+3)}{(a+3)(a-3)} = \frac{12}{a-3}

\frac{12}{a-3} : \frac{6}{a-3} = \frac{12(a-3)}{6(a-3)} = 2

Значение выражения не зависит от параметра а.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика